Faktor risiko yang mempengaruhi length of stay pasien kanker solid dengan febrile neutropenia pasca kemoterapi neoadjuvant/terapeutik di Ruang Isolasi RSUP Sanglah, Bali - Ronald Natawidjaja; Ida Bagus Tjakra Wibawa Manuaba; Putu Anda Tusta Adiputra (Intisari Sains Medis, 2019)
Background. Febrile neutropenia is a common complication in patient undergoing chemotherapy. Length Of Stay (LOS) is an important marker for disease severity and use of medical resources in febrile neutropenia. This study was done to find the risk factor affecting length of stay in solid cancer patients with febrile neutropenia post neoadjuvant/therapeutic chemotherapy.Method. This is a case control study without matching. Age ≥ 60 years, (Absolute Neutrofil Count) ANC level < 1,5 μL , comorbid,  Hb level <10 gr/dl, and albumin < 3 gr/dl, were related to LOS ( ≤ 5 days and > 5 days). Univariate (chi square) and multivariate (logistic regression) were used to analyse the statistic.Results. Forty six patients met inclusion-exclusion criteria were included in this study. ANC level in all patients were < 1,5 μL (100%). Hb level <10 gr/dl is statistically significant (P<0.05), whereas  age ≥ 60 years, and comorbid, albumin level < 3 gr/dl were not is statistically significant (P>0.05).Conclusion. Hb level < 10 gr/dl is the risk factor for LOS > 5 days in solid cancer patients with febrile neutropenia post neoadjuvant/therapeutic chemotherapy.